Secular trends in cardiovascular risk factors among urban and rural populations in Tamil Nadu, India – An ancillary analysis of the STRiDE-I study. (August 2021) - Nanditha, Arun; Susairaj, Priscilla; Raghavan, Arun; Satheesh, Krishnamoorthy; Vinitha, Ramachandran; Snehalatha, Chamukuttan; Ramachandran, Ambady
Abstract: Aims: To study changes in cardiovascular (CV) risk factors; hypertension (HTN), dysglycaemia (DG) and dyslipidaemia (DL) and their interrelationship, in urban and rural Southern India, in a decade. Methods: Epidemiological data of a city (Chennai, n = 2192(2006), n = 3850(2016)) and peri -urban villages (Panruti, n = 2584 (2006), n = 2468 (2016)) among persons aged ≥ 20 years in 2006 and in 2016 were analysed. Age-standardized prevalence, prevalence ratios and interrelationships of HTN, DG and DL and effect of time in years, age, gender and obesity were calculated using Poisson regression analyses. Results: Response rates in urban and rural areas were 86.5% and 87.6% respectively. Mean age, general obesity (GO), abdominal obesity (AO), total calories and carbohydrate intake increased in both populations (p < 0.0001). Rural population had lower BMI than the urban but had higher AO, particularly among women. Physical activity decreased only in the urban population. HTN increased in urban population; in both, proportion of known HTN decreased, DG and DL increased. Conclusions: In both populations, GO, AO, DG and DL increased; AO and DL were more common among rural women. HTN did not increase in the rural population. The risk factors increased rapidly even in rural areas projecting the impact of urbanisation on the CV burden.